The wettability of complete denture base materials constructed by conventional versus digital techniques: an in-vitro study - Kenda I. Hanno; Nayrouz Adel Metwally (BMC, 2024)
Abstract Background Decreased salivary flow can make the patients uncomfortable with their complete dentures and affects the retention of the dentures. Milling and 3D printing have become an alternative to conventional denture construction techniques. The goal of this study was to evaluate the effect of conventional and digital techniques of the complete denture construction on the denture surface wettability with distilled water and saliva substitute before and after thermocycling. Methods A total of 30 specimens were utilized in the present study. Specimens were divided according to the construction techniques into 3 groups (n = 10 each). Group I: Heat-polymerized polymethylmethacrylate (PMMA) group, group II: Milled group, and group III: 3-dimensional (3D)-printed group. All the specimens were subjected to 2000 cycles of thermal aging in a thermocycler. The wettability of all specimens to water and saliva substitute was measured via a contact angle goniometer (Olympus TGHM, Rame-hart Inc, USA) before and after thermocycling. Descriptive statistical analysis, plots, and the Shapiro-Wilk test were used to verify normality for each variable. One-way ANOVA was used to compare the 3 study groups, while paired samples t-test was used to compare the differences within each group (P < .05). Results The smallest contact angle of drop of water to the denture base specimens before and after thermocycling were recorded in the milled group (53.0 ± 4.77 and 50.27 ± 2.30, respectively), followed by the heat polymerized PMMA group (85.65 ± 4.71 and 65.06 ± 2.27, respectively), and the 3D-printed group (91.34 ± 6.74 and 90.86 ± 8.57, respectively). While the smallest contact angle of drop of saliva substitute to denture base specimens was recorded in the milled group (56.82 ± 2.29 and 34.85 ± 7.51, respectively), followed by the 3D-printed group (72.87 ± 4.83 and 58.14 ± 9.58, respectively) and the heat polymerized PMMA group (83.62 ± 4.12 and 67.82 ± 4.93, respectively). There was statistically significant difference between the groups (P < .05). A significant decline in the average contact angle of drop of saliva has been reported in all groups after thermocycling. The contact angle values differed significantly between saliva substitute and distilled water in both 3D-printed and milled groups after thermocycling (P < .001). Conclusions The milled denture base material presented the best wettability to water and saliva substitute than the 3D-printed and the heat-polymerized PMMA materials. Saliva substitutes improve the wetting ability of denture base materials manufactured by CAD/CAM compared with water.